2023
DOI: 10.1007/s12020-023-03520-6
|View full text |Cite
|
Sign up to set email alerts
|

Screening for primary aldosteronism on and off interfering medications

Xiaoyu Li,
Jiayu Liang,
Jinbo Hu
et al.

Abstract: To determine whether antihypertensives will affect diagnostic accuracy of the ARR to an extent that is clinically relevant. MethodsCon rmatory tests were used to con rm or exclude PA diagnosis. Area under the receiver operating characteristic curve (AUC), speci city and sensitivity of ARR performance in different conditions were calculated. Results208 PA and 78 essential hypertension (EH), and 125 PA and 206 EH patients, were included in the retrospective and prospective cohort, respectively. AUC of ARR on int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…A relatively small prospective study of 27 patients with PA and 151 patients with essential hypertension found no significant difference in the area under the receiver operated curve of the ARR on or off interfering medications when using a cutoff of 91 pmol/mU [ 22 ]. However, a larger cohort study of 331 patients (125 with PA and 206 with essential hypertension) who had ARR measured on and off interfering medications demonstrated an overall decrease in renin concentration and increase in ARR following cessation of interfering medications [ 23 ]. While on interfering medications (except β-blockers), a lower ARR cutoff of 27 pmol/mU showed comparable sensitivity and specificity to an ARR threshold of 54 pmol/mU off interfering medications.…”
Section: Case 1 Discussion: Impact Of Antihypertensive Medications On...mentioning
confidence: 99%
“…A relatively small prospective study of 27 patients with PA and 151 patients with essential hypertension found no significant difference in the area under the receiver operated curve of the ARR on or off interfering medications when using a cutoff of 91 pmol/mU [ 22 ]. However, a larger cohort study of 331 patients (125 with PA and 206 with essential hypertension) who had ARR measured on and off interfering medications demonstrated an overall decrease in renin concentration and increase in ARR following cessation of interfering medications [ 23 ]. While on interfering medications (except β-blockers), a lower ARR cutoff of 27 pmol/mU showed comparable sensitivity and specificity to an ARR threshold of 54 pmol/mU off interfering medications.…”
Section: Case 1 Discussion: Impact Of Antihypertensive Medications On...mentioning
confidence: 99%
“…The term “hormone” is occasionally expanded to cover substances made by cells that influence other cells nearby (paracrine signalling) or within the same cell (autocrine or intracrine signalling). Hormones produced by glandular cells travel through the circulatory system to target distant organs, influencing physiology and behaviour [ 96 ]. Key glands in the endocrine system include the hypothalamus, pituitary, thyroid, thymus, adrenal glands, pancreas, ovaries, and testes.…”
Section: Introductionmentioning
confidence: 99%